Effect of prenatal diagnosis of the vascular ring on perinatal management and treatment - A. Pavlova (Ukrainian Journal of Cardiovascular Surgery, 2018)
Objective. The purpose of the study is to create an algorithm for perinatal management of patients with prenatal diagnosis of the vascular ring (VR).Materials and methods. From 2004 to 2017 was performed 7740 primary fetal echocardiograms. Since 2016 was performed 21 fetal magnetic tomograms (MRI) in the diagnosis of VR.Results and discussion. In 70 (0.9%) cases was diagnosed VR. Two children had symptoms of compression of the trachea and esophagus immediately after birth; the others children had gradually increased symptoms since the 3rd month of life. The symptoms were noted in 13 children. After analisis the algorithm for perinatal management of patients with prenatal diagnosis of the VR has created. The absence of compression of the trachea on the fetal MRI allows us to plan births in the regional delivery department. If child hasn’t no symptoms after birth, we plane the surgical treatment with tracheal compression on computed tomography (CT) more than 30%. If child has symptoms, we plane an urgent consultation at the Center. The presence of compression of the trachea on the fetal MRI require births near the cardiosurgical center. If children has symptoms, we plane the surgical treatment. The other congenital heart disease (CHD) and VR treat at the same time.Conclusions. When the new algorithm for managing patients with VR will be introduce, the level of care for children with VR will be higher.